الرقابة القضائية على السلطة التقديرية و أساليب الحد منها - العموري, محمد رسول (Latakia University Journal - Economic and Legal Sciences Series, 2016)
تتمتع الإدارة العامة في معرض ممارستها لمهامها، بالعديد من الامتيازات، منها السلطة التقديرية، والتي تشكل روح الإدارة العامة وجوهرها، حيث تقتضي فاعلية الجهاز الإداري منح الإدارة هذه السلطة بغية مراعاة الظروف المتباينة والمتغيرة وصولاً لتحقيق الصالح العام. ويسلك المشرع حين يمنح الإدارة سلطة معينة أحد أسلوبين: فهو إما أن يحدد الشروط والضوابط التي ينبغي على الإدارة إتباعها عند مباشرة اختصاصاتها، فتكون سلطتها في هذه الحالة مقيدة، ويكون عملها مقصوراً على تطبيق القانون على الحالات التي تستوفي شروط هذا التطبيق. أو أن يترك للإدارة حرية التصرف لتقرر بمحض إرادتها، فيكون لها سلطة تقدير زمن وكيفية وملائمة مزاولة اختصاصاتها ومباشرة صلاحياتها دون قيود. ومن المفيد القول هنا أن الرقابة القضائية على تصرفات الإدارة لم تكن على درجة واحدة، بل تتسع وتضيق بحسب الركن الذي يعمل عليه القاضي رقابته، فيتمتع القاضي الإداري برقابة واسعة في مجال الأركان المقيدة في القرار الإداري، بينما تضيق رقابته إلى حد ما في مجال الأركان التقديرية، وكي لا تتحول السلطة التقديرية إلى عمل سيء يهدد حقوق الأفراد وحرياتهم، فقد توسعت رقابة القضاء الإداري على نطاق الملائمة في اتخاذ القرارات الإدارية، من خلال اعتماد نظريات متطورة تمثلت في نظريتي الخطأ البين والموازنة بين المنافع والأضرار. The public administrationenjoys in the exercise of its functions exhibition, many of the privileges which the discretionary power, which constitutes the spirit and essence of public administration, where the effectiveness of the administrative system requires grant administration, this power in order to take into account the varying and changing conditions in order to achieve the common good. And exhibits legislator while giving management the authority of certain one of two methods: it is either to determine the conditions and controls that management should follow when direct competence, authority shall be restricted in this case, and their work is limited to the application of the law to cases that meet the requirements of this application. Or be left to the management discretion to decide voluntarily, so have the power to estimate the time and how to engage in appropriate terms of reference and powers directly without restrictions. It is useful to say here that the judicial control over the administration's actions were not all on one level, but it is expanding and narrowing according corner which operates the judge supervision, vimta administrative judge supervision and wide in the field of restricted Chiefs of the administrative decision, while supervision narrowed somewhat in the field of Staff discretion, discretion order not to turn into a bad action threatens the rights and freedoms of individuals, it has expanded the administrative control of the elimination of appropriate management decisions scale, through the adoption of advanced theories represented in my theory wrong Albin and the balance between the benefits and damages.